1997
DOI: 10.1111/j.1754-4505.1997.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Interplak® and manual toothbrushes in a population with mental retardation/developmental disabilities (MR/DD)

Abstract: A major dental problem confronting persons with mental retardation/developmental disabilities (MR/DD) is poor dental hygiene, which can result in an increased incidence of gingivitis and periodontal disease. Studies indicate that the most obvious reason for the poor oral hygiene of such persons is their inability to clean the oral cavity adequately. The objective of this study was to determine whether there was a difference in the oral health between a group of residents with MR/DD using the Interplak and a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The differences between these studies with the results of the present study may be due to different factors: the choice of indices, the provision of dental prophylaxis during the study (Carr et al. , Dogan et al. ), the lack of randomization (Dogan et al.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The differences between these studies with the results of the present study may be due to different factors: the choice of indices, the provision of dental prophylaxis during the study (Carr et al. , Dogan et al. ), the lack of randomization (Dogan et al.…”
Section: Discussionmentioning
confidence: 66%
“…Conversely, some studies have shown significant advantages of different powered toothbrushes, when compared to manual toothbrushes, for GI (Carr et al. ) or for PlI (Carr et al. , Kaschke et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11] While the periodontist will prescribe a treatment plan, the control of the outcome, to a significant degree, is subject to the abilities, desires, and interests of the patient and, in the case of individuals with disabilities, the parent and/or other caregivers. Related concerns to be considered when developing a treatment plan for patients with disabilities:…”
Section: Why Periodontics?mentioning
confidence: 99%